Examination of Dominant Factors Affecting The Decision To Purchase Personal Medical Devices - Atmaja, Ni Putu Cempaka Dharmadewi; Puspitawati, Ni Made Dwi; Ribek, Pande Ketut (International Journal of Applied Science and Sustainable Development (IJASSD), 2024)
This study aims to analyze the effect of product quality, price perception, advertising and distribution channels on purchasing decisions for personal health devices. In addition, this study also aims to determine the dominant factors that influence purchasing decisions for medical devices. This research was conducted in Denpasar City by taking a research sample of 100 (one hundred) people using purposive sampling technique. This study uses multiple linear regression analysis techniques, t test and F test and test of determination. The result of the research is product quality, price perception has a positive and significant effect on purchasing decisions, while distribution channels have no significant effect on purchasing decisions. The implication of this research is that manufacturers who provide medical devices must be able to carry out price strategies in improving purchasing decisions and controlling market share in the health industry.